The Effectiveness of a New School-Based Media Literacy Intervention on Adolescents’ Doping Attitudes and Supplements Use - Lucidi, Fabio; Mallia, Luca; Alivernini, Fabio; Chirico, Andrea; Manganelli, Sara; Galli, Federica; Biasi, Valeria; Zelli, Arnaldo (Frontiers in Psychology, 2017)
The aim of the study was to evaluate the effectiveness of a media literacy intervention targeting, for the first time, the specific topic of Performance and Appearance Enhancing Substances (PAESs) use in high-school students. Overall, 389 students (52% male) aged between 13 and 19 years (mean = 16.56 year; SD = 1.26) participated to a media literacy intervention (i.e., “intervention group”) while 103 students aged between 14 and 19 year (mean = 16.10 year; SD = 1.38) were considered as the control group (i.e., “control group”). In two separate occasions over the course of six consecutive months, students in both groups filled out a set of questionnaires which included measures of social-cognitive beliefs (i.e., attitudes, subjective norms, intentions) and a self-reported measure of retrospective use of doping (Yes/No) and supplements (Yes/No). Compared to students in the control group (Mean(time1) = 1.96; SD(time1) = 0.85; and Mean(time2) = 2.09; SD(time2) = 0.94), intervention students on average expressed relatively stronger attitudes against doping use over time (Mean(time1) = 2.2; SD(time1) = 0.85; and Mean(time2) = 2.05; SD(time2) = 0.82). Students in the latter group also showed a statistically significant decrease in self-reported supplement use (Use(time1) = 6.7%; Use(time2) = 3.8%; p = 0.05, McNemar Test). Interestingly, albeit marginally significant, students in the control group showed a relative increment in the self-reported use of supplements over time (Use(time1) = 4.9%; Use(time2) = 8.7%; p = 0.22, McNemar Test). Overall, the media literacy intervention investigated in the present study was effective in decreasing adolescent student’s positive attitudes toward doping use and in reducing the use of legal PAES. These findings supported the generalizability and the usefulness of a media literacy approach in the specific field of PAES.